Iron Precipitation in Sulphuric Acid Under Pressure Oxidation Conditions at Elevated Temperatures (ABSTRACT PAGE) - Rhulani F. Maluleke; Francis W. Petersen; Allan Nesbitt; John H. Marsh; Johann de T. Steyl (International Mineral Processing Congress, 2003)
"Pressure leaching of chalcopyrite and nickeliferrous pyrrotite at temperatures between 105 and 200 ºC has been proposed as a potentially viable route for the extraction of mineral elements from sulphide concentrates. In general, these concentrates contain iron, and the economic success of the processes is partially dependent on the choice of the environmentally acceptable iron-removal technique. One of the most widely used methods for the removal of iron from sulphate liquors is precipitation as hematite, goethite, or jarosite. The nature of the iron precipitate formed, dictates downstream dewatering and residue treatment and disposal options. However, a better understanding of iron precipitation under the defined process conditions would consequently be of benefit in process design and optimization.This study investigated the precipitation of iron in the autoclave at temperatures between 105 and 200 ºC. The effects of temperature, acid concentration, iron concentration, and the presence of other metal cations on the nature and composition of the precipitates were determined."